AN ANALYSIS OF SURGICAL SHUNTS FOR THE MANAGEMENT OF PORTAL HYPERTENSION AT AGA KHAN UNIVERSITY HOSPITAL - Luqman, Zubair; Khan, Muhammad Rizwan; Alam, Mahboob; Atiq, Muslim; Sophie, Ziad (Journal of Ayub Medical College Abbottabad, 2004)
Background: The objective of our study was to analyze the outcome of surgical shunts for the management of variceal bleeding associated with portal hypertension. Methods: This was a retrospective analysis carried out at The Aga Khan University Hospital, Karachi of medical records from Jan 1991 - Dec 2001. The main outcome measures included morbidity and mortality associated with the surgical procedure, and the long term outcome in terms of recurrent bleeding. Results: A total of 30 patients underwent a shunt procedure during the study period. The mean age was 35 ± 13.75 years, with 22 (73%) males and 8 (27%) females. The indication for surgery was recurrent bleeding in 23 (77%) patients, and active bleeding refractory to endoscopic therapy in 7 (23%) patients. According to Child-Pugh classification, 19 (63%) patients were classified as Childs’ A, 7 (23%) as Childs’ B, and 4 (13%) as Childs’ C. The surgical procedure included distal splenorenal shunt in 25 (83%), central splenorenal shunt in 3 (10%), and portocaval shunt in 2 (7%) cases. Five patients expired within 30 days of surgical intervention with mortality rate of 16%. Three of these patients were Childs’ C, as compared to one each in Childs’ A and B, the difference being statistically significant. Similarly, the frequency of encephalopathy and recurrent bleeding was also significantly higher in patients with Childs’ class C. Conclusions: Surgical shunts may be considered as a reasonable alternative for long term control of recurrent variceal bleeding in patients with good hepatic reserve. Keywords: Variceal bleeding, Portal hypertension, distal splenorenal shunt